Kann Deutschland den Krisenländern der Eurozone helfen? - Hayo Reimers (Wirtschaftsdienst, 2018)
Trotz der guten wirtschaftlichen Lage in der Eurozone verzeichnen einige Krisenländer nach wie vor ein geringes Wachstum und eine hohe Arbeitslosigkeit. Diese Länder erhoffen sich von einer Erhöhung der Nachfrage in den wirtschaftlich erfolgreicheren Staaten eine Unterstützung ihres Aufschwungs. Die möglichen Spillovereffekte eines Anschubs beispielsweise aus Deutschland werden aber im Allgemeinen überbewertet. Wichtiger wäre es, wenn die Krisenstaaten durch interne Reformen ihre Wettbewerbsfähigkeit stärken würden. Zudem könnte sich eine Schwächung der deutschen Wettbewerbsfähigkeit durch steigende Löhne und Preise auch negativ auf sie auswirken. – – The economic situation of the eurozone has recently improved. Nevertheless, growth and employment fi gures of important member countries such as Italy, Spain and France demonstrate clearly that the crisis is not yet over. The weaker economies' request for support from their stronger neighbours, particularly Germany, is a constant element of political debate. Germany refuses to go along with demand-side-oriented investment programmes that are meant to produce positive spillover effects for its neighbour countrie s. Instead, the German government sticks to its austerity policy, claiming that the source of the eurozone's prolonged economic vuln erability can be found on the supply side, weakening those economies' international competitiveness. Relying on economic data analysis rather than politically motivated arguments, this paper focuses on the economic facts behind these two conflicting lines of argumentation.
Keywords: F33; F34; F42; H62; 330